The Implementation of Creative Entrepreneurship and Self-Reliance Values Through Role Playing Method in Kindergarten (Research in Belia Kindergarten B Group-Semarang) - Tasuah, Neneng; Windiarti, Rina (Universitas Negeri Semarang, 2016)
Role playing method is very effective to be used for introducing values to children. If the child is already used to determine these values then it will be easier to implement them. And if it is done in a fun way, that will be memorable for children. Teachers are constantly seeking creative new approaches in solving problems, not fixated on a certain way that is monotonous, but choose other appropriate variations. Role play is one alternative that can be taken. In this case, role play is used to apply the values of entrepreneurship to students. Under these conditions, the formulation of the problem to be studied is how the implementation of the values of creative entrepreneurship and self-reliance through role playing method in the kindergarten. This study uses a qualitative method. Reasons to use qualitative research was because the object is natural, in addition to the presentation of data using descriptions that describe the real situation. The results of this study are in the center of role play, before the event takes place, the teacher provides an explanation of the activities to be carried out. Teachers offered the role to be played to the child. Teachers also provide information on what items are to be used in the role-play activity. Then the teacher gives children the freedom to play their respective roles. Teachers record all the child's behavior. From these activities children will show their creative and self-reliant value.